“GONG CETING” GERAKAN KOLABORATIF PERGURUAN TINGGI DAN PEMERINTAH DALAM UPAYA PENURUNAN STUNTING - Ika Purnamasari; Candra Dewi Rahayu; Fibrinika Tuta Setiani; Nazila Nugraheni; Anisa Ell Raharyani (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The prevalence of stunting in Wonosobo Regency, which ranks the highest at 28.1%. This condition requires serious attention from various parties including universities and stakeholders. The impact of stunting not only affects physical growth, but what is more dangerous is the effect on brain growth that is not maximized. The purpose of this community service by Faculty of Health Sciences of UNSIQ team is to empower the community according to its capacity in order to accelerate the reduction of stunting in Wonosobo. The Gong Ceting program method in 10 selected villages was carried out through planning, implementation and evaluation stages. Activities in the form of training to improve TPK skills in data collection & identification of stunting risks, anthropometric measurement training for Posyandu cadres, training for cadres and families at risk of stunting on the preparation of healthy family menus, training and selection of Youth Ambassadors, Pakwalisanak Gong Ceting formation. Results and Conclusions All activities can be carried out well thanks to the cooperation of all parties and the support of the district government to the village government levels. In general, gong ceting activities can increase community knowledge and skills in efforts to prevent and handle stunting.